The comparative evaluation of the effects of quercetin, α‐tocopherol, and chlorhexidine dentin pretreatments on the durability of universal adhesives - Marzieh Moradian; Maryam Saadat; Fatemeh Sohrabniya; Mohammad Afifian (Wiley, 2022)
Abstract Objective The aim of this study was to evaluate and compare the effects of chlorhexidine, quercetin, and α‐tocopherol on the shear bond strength of universal adhesives in the short (24h) and long term (6 months). Material and Methods Ninety‐six extracted sound molars were collected and divided randomly into four groups: control (no treatment), 2% chlorhexidine, 10% α‐tocopherol, and 1% quercetin. The solutions were prepared and applied to the teeth for 60 s, followed by application of All‐Bond universal adhesive and composite build‐up. Half of the specimens in each group (n = 12) were tested for shear bond strength (SBS) after 24 h of storage and the other half were kept in distilled water for 6 months and then tested for shear bond strength. The shear bond strength test was performed and the failure modes were determined using a stereomicroscope. The data were analyzed using two‐way analysis of variance and Tukey's post hoc tests with p ˂ .05 as the significance level. Results The results of the two‐way analysis of variance test showed that there was no significant difference in immediate SBS, and after 6 months, α‐tocopherol had the lowest SBS in comparison to the control and CHX subgroups (p < .05). The t‐test showed that the shear bond strength in the α‐tocopherol and quercetin groups was significantly decreased after 6 months. Conclusion It can be concluded that the solutions used in this study had no adverse effect on immediate SBS. After 6 months, the CHX could preserve SBS in comparison to other groups.